Beclin 1 - Molejon, Maria Ines (2012)
Beclin 1/ATG6/Vps30 (UniProtKB/Swiss-Prot Q14457) is a 450 amino-acids length protein, with three domains; BH3 (aminoacid 114 to 123), Coiled Coil domain (CCD; aminoacid 144 to 269) and the Evolutionarily Conserved Domain (ECD; aminoacid 244 to 337). BH3 proteins are part of the Bcl-2 family; they are pro-apoptotic damage sensors that play an important role in protecting against cancer (1). The BH3-only domain of Beclin 1 can interact with Bcl-2 and Bcl-XL (2;3). Both cellular and viral Bcl-2 (vBcl-2), or more specifically ER-targeted Bcl-2, inhibit Beclin 1-dependent autophagy by interfering with the Beclin 1-PtdIns 3-kinase interaction (PI3K) and the Beclin 1-associated PI3K activity (3,4). The interaction between Bcl-2 and Beclin 1 is greatly reduced upon starvation, which suggests that the dissociation of Bcl-2 from Beclin1 is important for activating autophagy. We demonstrated that, VMP1 (Vacuole Membrane Protein 1) displaces Bcl-2 from Beclin 1, partitioning Beclin 1 to the autophagic pathway (Molejon et al., Sci Rep. 2012; In press).